Formation mechanism of Fe-Mo master alloy by aluminothermic reduction of MoS2-Fe2O3 in the presence of lime - Golmakani, Mohammad Hossein; Vahdati Khaki, Jalil; Babakhani, Abolfazl (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
The reaction mechanism of MoS2-Fe2O3 aluminothermic reduction in the presence of lime using microwave-assisted combustion synthesis method was surveyed. Achieving technical feasibility in one-step production of ferromolybdenum along with sulfur removing in solid form are the main features of this novel process. Simultaneous Preliminary thermo-analytical investigations DSC/TGA and X-ray diffraction experiments during the heating process of 0.42 MoS2 +1.14 Al + 0.29 Fe2O3 +0.84CaO demonstrated four key sequential endothermic and exothermic reactions at 420, 540, 660, and 810 oC. The most noteworthy reactions involve evaporation of moisture and volatile matter, molybdenite roasting, simultaneous production of lateral compounds such as CaMoO4 and CaSO4, aluminum melting transition, and final termite reaction. Kinetics procedure of the system was conducted using a classical model-free approach by Kissinger–Akahira–Sunose (KAS) method. In this study, the activation energy was determined about 106.4 (kJ.mol-1) for thermite reaction in the temperature range of 810 to 918 oC.